Digital Versus Paper Reading Processes and Links to Comprehension for Middle School Students. (August 2020) - Goodwin, Amanda P.; Cho, Sun-Joo; Reynolds, Dan; Brady, Katherine; Salas, Jorge
This study explores digital and paper reading processes and outcomes for 371 fifth to eighth graders completing a reading task similar to standardized testing. Results showed students highlighted and annotated more when reading the paper versus digital text. Also, reading on paper versus digitally was slightly supportive of reading comprehension for the longer section of text. For behaviors, digital highlighting and looking back at the paper text were supportive of reading comprehension, whereas paper highlighting was negatively related, likely because paper highlighting tended to occur often outside of important areas of the text. Paper and digital annotating, online dictionary use, and digital look-back did not link to comprehension, when controlling for other covariates. Links to theory, research, and practice are discussed.